Ukrainian Black Grouse Tetrao tetrix: Genetic Diversity and Population Structure. Issue 6 (1st December 2015) - Pavlovska, Mariia; Höglund, Jacob
Abstract : We studied neutral (microsatellite) and adaptive (MHC) genetic diversity of two Ukrainian populations of black grouse Tetrao tetrix to fill a gap in the data on the diversity of European populations of this species. We found that Ukrainian populations are more diverse than recently fragmented central European ones and also highly differentiated from these populations. Both studied populations in Ukraine, the northern and the Carpathian, did not show any signs of recent bottleneck events. The population structure among Ukrainian black grouse was more pronounced for neutral variation than for adaptive MHC diversity, suggesting that a common selective force has led to balancing selection shaping the MHC diversity. The MHC differentiation among the two studied regions was still high (Dest = 0.454), which could be a sign of local adaptation as a response to shifting balance in space. Thus, we suggest that the northern and the Carpathian black grouse populations should be treated as separate Management Units (MU). The black grouse population in the Carpathian Mountains appeared to be more diverse than the one in the north in terms of neutral genetic variation, whereas in terms of adaptive variation the two populations vary in diversity depending on the method of scoring diversity. Therefore, we suggest that the Carpathian Mountains could have been a refuge for the black grouse during the last glaciation.